Creation of the new architecture of security as a factor of emerging multipolarity in theWorld. Pozition of Germany - V. P. Terekhov (Vestnik MGIMO-Universiteta)
The article represents analysis of debate opened up in Germany over the proposal made by the RF President D. Medvedev on the newsecurity structure in Europe and сonclusion of an appropriate agreement. The author reviews reaction to this proposal received from officials and main political forceswhich determine the course of foreign activity ofGermany and elaborate its position on actual international issues.